2007
DOI: 10.1017/s1431927607070055
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Dissects the Hierarchy of Genome Architectures in Eukaryote, Prokaryote, and Chloroplast

Abstract: Because of its applicability to biological specimens (nonconductors), a single-molecule-imaging technique, atomic force microscopy (AFM), has been particularly powerful for visualizing and analyzing complex biological processes. Comparative analyses based on AFM observation revealed that the bacterial nucleoids and human chromatin were constituted by a detergent/salt-resistant 30-40-nm fiber that turned into thicker fibers with beads of 70-80 nm diameter. AFM observations of the 14-kbp plasmid and 110-kbp F pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The application of AFM to the organization of DNA within bacteria revealed the role of RNA in assembly of the 30–40-nm nucleoid fiber. However, RNA is not involved into the assembly of eukaryotic 30-nm chromatin (Ohniwa et al 2007). …”
Section: Chromatin Study With Afmmentioning
confidence: 99%
“…The application of AFM to the organization of DNA within bacteria revealed the role of RNA in assembly of the 30–40-nm nucleoid fiber. However, RNA is not involved into the assembly of eukaryotic 30-nm chromatin (Ohniwa et al 2007). …”
Section: Chromatin Study With Afmmentioning
confidence: 99%
“…These lines of evidence suggest that the 30-to 40-nm thin fiber and the 70-to 80-nm granular fiber are the fundamental structural units of eukaryotic chromosomes; these fibers are relatively stable in a wide range of experimental conditions. Recent reports have demonstrated that these hierarchical structures exist in both eukaryotes and prokaryotes [35] and that nascent single-stranded RNAs are part of the 30-80 nm fiber structures [62,63].…”
mentioning
confidence: 99%
“…Furthermore, some bacterial and mitochondrial man, 2010)). Recent reports suggest that in addition to topoisomerases and NAPs, RNA also plays an important role in the organization of nucleoid DNA-protein fibers (Ohniwa et al, 2007).…”
Section: Nucleoidsmentioning
confidence: 99%